Effects of out-of-plane eccentric axial compression on in-plane hysteretic behavior of SC walls. (October 2020) - Guo, Quanquan; Zhang, Peiyao; Fu, Yiqing; Ke, Fei
Highlights: 4 SC walls subjected to combination effect of in-plane and out-of-plane loads were tested. Fiber element model was used to obtain interaction surface N-Mx -My . A simplified formula is put forward to predict Mx /M0x –My /M0y curves. Abstract: Steel-concrete composite (SC) walls may be subjected to simultaneous in-plane (IP) and out-of-plane (OOP) loads in some civil and industrial buildings. However, there are few studies and no design guideline for SC walls under such load conditions. In this paper, four SC wall specimens were designed and tested to investigate the effects of OOP loading on IP hysteretic behavior. During the experiment, a constant eccentric axial compressive force was applied to the top of the specimen, which generated an OOP bending moment. The variables considered in the experiments were the eccentric distance and the axial compression ratio. All four specimens demonstrated characteristics of the flexural failure mode. The IP bearing capacity and deformation capacity of the specimens were significantly reduced due to the influence of OOP loading. A nonlinear analysis program based on fiber model method was presented to calculate the IP and OOP bearing capacity under different load combinations. An interaction surface, N-Mx -My, and a simplified formula were developed as a simplistic tool to consider simultaneous IP and OOP bending moment.